The role of attention deficit hyperactive disorder in developing substance use disorder: a case report - Md Rosli, Ahmad Nabil MR; Subbiah, Rakesh; Zakaria, Hazli (Malaysian Psychiatry Association, 2015)
Objective: Individuals with ADHD are known to have more risk of developing substance use disorder (SUD). However the underlying mechanisms behind it are not straightforward. Method: We report a case of an adult with ADHD, who has a long standing history of polysubstance use, since the age of 10. He had multiple relapses, even after numerous efforts undertaken to keep him drug-free. Result: ADHD symptoms were not optimally treated during admission. He had preference towards opioid-based and amphetamine-type substances in order to attain euphoria. Conclusion: Taking into account the biological and psycho-social condition of this man, we discussed the role of ADHD from the perspective of dysfunctional rewards system and other possible factors in explaining his drug-craving behavior. Keywords: Attention-deficit Hyperactive Disorder (ADHD), Substance Use Disorder (SUD), Adult